Light-controllable recellularized ventricular and atrial tissues. (14th October 2021) - Ghiringhelli, M; Gruber, A; Abboud, Y; Shiti, A; Ballan, N; Huber, I; Arbel, G; Gepstein, L
Abstract: Introduction: Construction of three-dimensional ventricular and atrial patches using decellularized extracellular matrix could allow the creation of "organ-like" structures for disease modeling, drug testing and regenerative medicine applications. To engineer functional artificial anatomical hearts several obstacles need to be overcome including generation of chamber-specific cells, prevention of immune reaction and donor/host tissue electrical coupling. Purpose: In order to tackle these challenges we aimed to combine human induced pluripotent stem cell (hiPSC) technology, developmental biology inspired differentiation system to generate chamber-specific cardiomyocytes, decellularization/recellularization processes, and optogenetics utilizing light-sensitive ion channels to generate light-controllable atrial/ventricular tissue engineered patches. Material and method: Atrial and ventricular patches of adult rats were decellularized using 1% SDS, 3% triton-X. The decellularized scaffolds were then recellularized with hiPSC- derived cardiomyocytes (2x107 atrial or ventricular cells). Adenoviral transduction was used to express the light-sensitive cationic channel ChR2 in the tissue engineered constructs. Results and discussion: Eight days after cell seeding, we observed the development of spontaneous contraction of the atrial/ventricular tissues. Immunostaining for atrial (Cx40) or ventricular (MLC-2V) markers, gene expression, action-potential morphology, and the response to chamber-specific pharmacology confirmed the atrial/ventricular specific identity of the patches. Histological examination confirmed the preservation of the macro/micro- atrial/ventricular anatomical features in the generated chamber-specific recellularized patches. Optical mapping, using an EM-CCD camera, was used to characterize the conduction and repolarization properties of the generated tissues. The engineered patches could be paced and their electrical activity controlled by either electrical or optogenetic stimulation. Finally, arrhythmogenic reentrant arrhythmias could be induced in the tissue models and terminated by using optogenetic stimulation ("optogenetic-defibrillation"). Conclusions: Three-dimensional light-sensitive chamber-specific engineered heart patches could be generated that could be controlled and manipulated through electrical and light pacing. These tissue could be used for several pathophysiological, drug testing, disease modeling and regenerative medicine applications. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): H2020-ERC-COG